If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(2m + 7) = 2 + 4m + -12 Reorder the terms: 15 + -1(7 + 2m) = 2 + 4m + -12 15 + (7 * -1 + 2m * -1) = 2 + 4m + -12 15 + (-7 + -2m) = 2 + 4m + -12 Combine like terms: 15 + -7 = 8 8 + -2m = 2 + 4m + -12 Reorder the terms: 8 + -2m = 2 + -12 + 4m Combine like terms: 2 + -12 = -10 8 + -2m = -10 + 4m Solving 8 + -2m = -10 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 8 + -2m + -4m = -10 + 4m + -4m Combine like terms: -2m + -4m = -6m 8 + -6m = -10 + 4m + -4m Combine like terms: 4m + -4m = 0 8 + -6m = -10 + 0 8 + -6m = -10 Add '-8' to each side of the equation. 8 + -8 + -6m = -10 + -8 Combine like terms: 8 + -8 = 0 0 + -6m = -10 + -8 -6m = -10 + -8 Combine like terms: -10 + -8 = -18 -6m = -18 Divide each side by '-6'. m = 3 Simplifying m = 3
| (3x-35)=130 | | 27.95(2)+0.32(m)=250 | | X^2+10+41=0 | | .9x-2.1+.4=.2(5-X) | | (3x-10)+(5x-10)+(2x)=180 | | 23.95(4)+0.32(m)=200 | | -3(y+3)=2y-3 | | j=8-j | | -5.5+-4y=x | | 2(5x-34)+(.67-45x)=345 | | 5x+7-8=0 | | Log(5x+13)=0 | | 6-4z=-3-5z | | 1=112=223=33..11=? | | (5x+23)-56x=14x+.75 | | u^3-14u-32u=0 | | (4x-2)+(x+7)= | | 126=7(x+2) | | 24+p^2=159 | | x-6x-23=0 | | (5x+23)-56x= | | (x+2)=-5-2(x+3) | | (4x-2)+(x+7)+(x+7)=180 | | [10x]=-20 | | -10+4r=10+2r | | -8x+5=7-8x-2 | | rs-s=12 | | 6-(2.3x)-(2.7x)=21 | | -10y=-5y-10 | | 1=1111=1 | | x^3-9x^2+8x-3=0 | | -10x+18y=5 |